Company Websites: A New Measure of Disclosure - BOULLAND, ROMAIN; BOURVEAU, THOMAS; BREUER, MATTHIAS (Journal of Accounting Research, 2026)
We propose a new measure of firms' disclosure based on company websites, which are widely available and contain a wealth of information. For a sample of U.S. public firms, we construct our disclosure measure using historical website data, validate it by correlating it with extant measures of disclosure and information asymmetry, and explore its determinants. We then apply our measure to the study of U.S. private firms' disclosure and French firms' compliance with a nonfinancial disclosure mandate. Our applications illustrate that our website‐based measure provides a useful complement to extant measures of disclosure, which are more narrowly focused on investors in public capital markets.